Guns akimbo [videorecording (DVD)] - Howden, Jason Lei, 1979-; Radcliffe, Daniel, 1989-; Weaving, Samara, 1992-; Liu, Chengyu, 1994-; Dennehy, Ned, 1965-; Bowler, Grant, 1968- (Lionsgate, 2020)
Miles's nerdy existence as a video game developer takes a dramatic turn when he inadvertently gets caught up as the next contestant with SKIZM, an underground gang livestreaming real-life death matches. While Miles excels at running away from everything, that won't help him outlast Nix, a killer at the top of her game.